Analysis of influencing factors and prognosis of early postoperative recurrence, secondary tumor and metastasis of oral squamous cell carcinoma - Tang, Haiyang; Hu, Feiyun; Li, Xinying; Song, Hongjie (Cellular and Molecular Biology, 2021)
Oral squamous cell carcinoma (OSCC) is one of the most common cancers in the world and it accounts for more than 90% of oral cancers. In this study, we tried to estimate the risk of early postoperative recurrence, secondary tumor and metastasis of OSCC to predict the patient's prognosis according to its clinical condition to help increase their survival by screening high-risk patients. 153 patients with OSCC who were over 40 years of age were studied during 1985-2020. The influencing factors included gender, race, stage of tumor progression, treatment method, histological grade and tumor location, date of diagnosis and death, which were analyzed by the Markov multi-state model. Also, their saliva was sampled to determine the amount of Matrix Metalloproteinase13 (MMP13). Following-up of patients for 60 months showed that one year after the end of treatment, the probability of death was almost the same for patients with early postoperative recurrence or secondary tumor, but after 5 years, patients with early postoperative recurrence are at higher risk of death. Also, the MMP13 amount in the saliva of patients showed that high levels of MMP13 belonged to metastasis of OSCC than early postoperative recurrence and secondary tumor. Therefore, patients with more amount of MMP13 are more involved in metastasis than early postoperative recurrence and secondary tumor. Approximate knowledge of OSCC patients' next state and time according to their clinical condition can be one of the ways of timely diagnosis and treatment and thus reduce their mortality rate.